2023
DOI: 10.1002/smll.202305479
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Nanoporous Ir/Ta2O5 Interfaces on Metallic Glass for Durable Acidic Water Oxidation

Yijing Qiao,
Min Luo,
Lebin Cai
et al.

Abstract: Although proton exchange membrane water electrolyzers (PEMWE) are considered as a promising technique for green hydrogen production, it remains crucial to develop intrinsically effective oxygen evolution reaction (OER) electrocatalysts with high activity and durability. Here, a flexible self‐supporting electrode with nanoporous Ir/Ta2O5 electroactive surface is reported for acidic OER via dealloying IrTaCoB metallic glass ribbons. The catalyst exhibits excellent electrocatalytic OER performance with an overpot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…As shown in Figure S25a, compared with fresh Ir−MnCo 2 O 4.5 , the peak position of Ir L 3 shifts to a higher energy after the long-term CP test, indicating that single Ir atoms gradually oxidized during the continuous OER process. 16,42 This phenomenon is consistent with the results observed by XPS. The corresponding Fourier transformed EXAFS spectrum is shown in Figure S25b.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Figure S25a, compared with fresh Ir−MnCo 2 O 4.5 , the peak position of Ir L 3 shifts to a higher energy after the long-term CP test, indicating that single Ir atoms gradually oxidized during the continuous OER process. 16,42 This phenomenon is consistent with the results observed by XPS. The corresponding Fourier transformed EXAFS spectrum is shown in Figure S25b.…”
Section: Resultssupporting
confidence: 92%
“…By normalization to the Ir loading at 1.50 V, the mass activity (MA) of integrated Ir–MnCo 2 O 4.5 is 57, which is 7 times greater than that of Com IrO 2 . Compared with previously reported OER catalysts, integrated Ir–MnCo 2 O 4.5 shows comparable MA (Table S9). In addition to MA, the lower overpotential and Tafel slope (Figure e and Table S10) make the integrated Ir–MnCo 2 O 4.5 electrocatalyst an ideal candidate for the OER.…”
Section: Resultsmentioning
confidence: 59%
“…3 helps to stabilize the oxidation state of Ir. Tan et al reported nanoporous Ir/Ta 2 O 5 catalysts for acidic OER, in which the electron-donating behavior of Ta 2 O 5 stabilized the high oxidation states of Ir and optimized the adsorption of OOH* intermediates on Ir sites during OER, thereby achieving high activity and stability 50. Liu et al synthesized a W 18 O 49−δ matrix-confined Ru solid solution oxide catalyst that exhibited good stability in acidic conditions for OER 51.…”
mentioning
confidence: 99%